From Urges to Action: Negative Urgency and Nonsuicidal Self-Injury in an Acute Transdiagnostic Sample - Peckham, Andrew D. (Arch Suicide Res, 2019)
OBJECTIVE: Urgency–rash action during strong emotion–is a robust correlate of nonsuicidal self-injury (NSSI). This study tested whether urgency is associated with time between NSSI urges and NSSI, and sought to replicate the finding that urgency is associated with NSSI history. METHODS: Participants attending a partial hospitalization program (N = 669) completed self-report measures of urgency, NSSI history and latency, and psychiatric symptoms. RESULTS: Consistent with previous research in clinical samples, rates of lifetime engagement in NSSI were high. Using logistic regression to predict short vs. long latency between urges and NSSI, no significant relationship emerged between negative urgency and latency to self-injure. Negative urgency more than doubled the likelihood of NSSI history (p < .001, OR = 2.39). In addition, exploratory analyses revealed several links between NSSI latency and negative urgency. CONCLUSION: Results confirm that urgency is robustly related to NSSI, yet also suggest that more research is needed to understand how urgency relates to the parameters of NSSI within those who self-injure. Use of retrospective self-report measures may limit the ability to test links between urgency and latency of NSSI.